Biennial review 2019: Commitment 6: Enhancing resilience to climate variability - Kurtz, Julie E.; Ulimwengu, John M. (International Food Policy Research Institute, 2020)
In line with the Maputo Declaration that established the Comprehensive Africa Agriculture Development Programme (CAADP) in 2003 and with the 2014 Malabo Declaration, African Union (AU) Member States pledged to conduct a continentwide Biennial Review (BR) to monitor and report on progress in achieving seven thematic commitments outlined in the Declaration. The inaugural 2017 BR Report, the first of its kind in Africa, was launched and endorsed by the AU General Assembly in January 2018. The second BR report was adopted at the AU General Assembly in February 2020.